P0283LONG-TERM FOLLOW-UP OF CRYOGLOBULINEMIC SYNDROME WITH RENAL INVOLVEMENT AFTER DAA. (6th June 2020) - Affatato, Stefania; Pollastri, Ester; Belotti, Elena; Zani, Roberta; Zaltron, Serena; Spinetti, Angiola; Castelli, Francesco; Scolari, Francesco
Abstract : Background and Aims: To date, the literature shows that HCV eradication with DAA leads to remission from HCV-related cryoglobulinemic syndrome (CS). The goal of our study is to evaluate the effect of DAA treatment on cryoglobulinemic kidney disease. Method: Since 2015, 58 patients (pts) have been treated in our Centre; among them we have selected 12 pts with active kidney disease at the time of treatment. Clinical manifestations, renal function and immunological tests were monitored during follow-up (range 6-48 months). Results: General characteristics of the population are shown in Table 1. At the time of treatment 6 pts had nephritic syndrome (sdr), 1 had nephrotic sdr and 5 pts had mixed nephritic-nephrotic sdr. It should be noted that 8/12 pts had been treated with Rituximab (RTX) in the 6 months preceding the DAA; despite that they had active disease at baseline. Ten out of 12 pts went into complete remission after HCV-eradication, 1 went into partial remission. One pt, never treated, did not respond clinically to HCV eradication and therefore underwent RTX therapy. Other 2 pt with a recent diagnosis of cryoglobulinemic syndrome came to our attention with a clinical picture of nephritic sdr: they'd never been treated with immunosuppressive therapy and get remission only whit HCV eradication. One pt, although complete CS remission, started hemodialysis for ESRD secondary to ADPKD. During follow-up 3 pts underwent CS relapse: 2 pts, one with lymphoma, were retreated with RTX after 12 and 48 months respectively; 1 pt, with type I cryoglobulinemia and clinical manifestation of vasculitis, died of acute disease reactivation in Cameroon after 9 months from the end of DAA. By evaluating the overall population there is a rapid and prolonged clinical response to DAA therapy, in particular a complete resolution of skin ulcers (Tab 2). Cryocrit decreases and C3 and C4 increase early and persistently after treatment; vice versa the rheumatoid factor does not undergo significant variations. Proteinuria is reduced at the end of the treatment (EOT) and shows a decreasing trend also afterwards; urinary sediment is drastically reduced at EOT and further decreases during follow-up up to the presence of only isolated urinary anomalies in almost all patients (Tab 3). Conclusion: The eradication of HCV, and therefore the removal of the immunological stimulus underlying the cryogloblinemic syndrome, appears to be crucial in the control of cryoglobulinemic glomerulonephritis, also after failure of RTX treatment. However, relapses at variable interval from DAA therapy do not allow us to lose these patients to follow-up even after several years from disease remission.